Analyses of seven new whole genome sequences of cassava brown streak viruses in Mozambique reveals two distinct clades: evidence for new species. (10th March 2019) - Amisse, J. J. G.; Ndunguru, J.; Tairo, F.; Ateka, E.; Boykin, L. M.; Kehoe, M. A.; Cossa, N.; Rey, C.; Sseruwagi, P.
Abstract : Cassava brown streak disease (CBSD) caused by Cassava brown streak virus (CBSV) and Uganda cassava brown streak virus (UCBSV) is a major constraint to cassava production in Mozambique. Full genome sequences of CBSD‐associated virus isolates contribute to the understanding of genetic diversity and the development of new diagnostic primers that can be used for early detection of the viruses for sustainable disease management. This study determined seven new whole CBSV genomes from total RNA isolated from cassava leaves with CBSD symptoms collected from Nampula and Zambezia in Mozambique. Phylogenetic analyses of the new genomes with published CBSV and UCBSV sequences in GenBank grouped the CBSV isolates from Mozambique into two distinct clades together with CBSV isolates from Tanzania. Clade 1 and 2 isolates shared low nucleotide (79.1–80.4%) and amino acid (86.5–88.2%) sequence identity. Further, comparisons within the seven new CBSV isolates, and between them and the single published complete CBSV sequence (CBSV_MO_83_FN434436) from Mozambique, revealed nucleotide sequence identities of 79.3–100% and 79.3–98%, respectively, and amino acid identities of 86.7–100% and 86.7–98.8%. In addition, using RDP4, a recombination analysis comprising all CBSV and UCBSV genome sequences from GenBank detect 11 recombination events. Using several comprehensive evolutionary models and statistical programs, it was confirmed that CBSV and UCBSV are distinct virus species, with an additional probable new species (clade 2).